On the Inequalities Concerning to the Polar Derivative of a Polynomial with Restricted zeros: Irshad Ahmad, Abdul Liman, Wali Mohammad Shah - Team, Support (Thai Journal of Mathematics, 2018)
In this paper, we prove an Lp-inequality concerning the polar derivative of a polynomial with restricted zeros.